2023
DOI: 10.1371/journal.pone.0293145
|View full text |Cite
|
Sign up to set email alerts
|

Diet-derived antioxidants and osteoporosis: A Mendelian randomization study

Haitao Li,
Lanlan Chen,
Chaofeng Yuan
et al.

Abstract: Background Antioxidants can prevent osteoporosis, but the association between serum antioxidants and the cause of osteoporosis remains unknown. We aimed to utilize Mendelian randomization (MR) to determine whether genetically predicted serum levels of diet-derived antioxidants can affect the risk of osteoporosis, to determine the effect of dietary supplementation of antioxidants. Methods Genetic variants associated with diet-derived antioxidants were selected from the genome-wide association studies. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, the credibility and broad applicability of these outcomes were limited by reliance on just two discrete datasets. Of particular relevance, the extensive osteoporosis-centric research endeavor, the GEFOS database, did not reveal any statistically discernible disparities in OP risk between β-carotene and γ-tocopherol levels (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…However, the credibility and broad applicability of these outcomes were limited by reliance on just two discrete datasets. Of particular relevance, the extensive osteoporosis-centric research endeavor, the GEFOS database, did not reveal any statistically discernible disparities in OP risk between β-carotene and γ-tocopherol levels (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…There is weak evidence that β-carotene levels are associated with increased LS-BMD in the current study. However, the results of a previous MR performed by li et al ( Li et al, 2023 ) showed that serum β-carotene levels significantly reduced OP risk. For the instrumental variables of β-carotene, we used more strict screening criteria ( p < 5 × 10 −8 and r 2 < 0.001), which helped us to make more reliable conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…SNPs with linkage disequilibrium (LD) were removed by stringent clumping criteria (kb = 10,000, r 2 = 0.001) to retain mutual independent instrumental SNPs. F-statistic was calculated by the formula (F = β 2 /SE 2 ) to appraise the potency of each SNP [ 35 , 36 ]. β stands for effect size, SE stands for standard error.…”
Section: Methodsmentioning
confidence: 99%